2018
DOI: 10.24071/llt.v21i2.1224
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment Literacy Development: A Student-Teacher�s Experiences in Teaching Practice Program

Abstract: The development of a student-teachers language assessment literacy was viewed through her experiences in conducting teaching practice in one of the senior high schools in Yogyakarta, Indonesia. An interview was conducted to explore the experiences taking place in the teaching-practice in relation to the language assessment literacy development. It was found out that the experiences were understood as mostly dealing with administrative tasks and there is a need of more knowledge in administrative matter in teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The importance of evaluation has set the alignment to be achieved in his study. Since this circumstance has a highly positive impact on educators, helping them to organize and strategize effective and efficient learning procedures and strategies for the future (Prasetyo, 2018). Evaluation is also a significant consideration in the final decision-making process because it is part of a systematic method that gathers information for all of the teaching staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of evaluation has set the alignment to be achieved in his study. Since this circumstance has a highly positive impact on educators, helping them to organize and strategize effective and efficient learning procedures and strategies for the future (Prasetyo, 2018). Evaluation is also a significant consideration in the final decision-making process because it is part of a systematic method that gathers information for all of the teaching staff.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation has been an essential component of the teaching and learning process for as long as it has been a part of the teaching and learning process itself, which is something that takes place all the time at every educational institution. This circumstance has a very positive impact on educators in terms of assisting them in organizing and strategizing effective and efficient learning procedures and strategies for the future (Prasetyo, 2018). Evaluation is also a significant consideration in the final decision-making process because it is part of a systematic method that gathers information for all of the teaching staff.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, LAL must be implemented correctly in the classroom (Fulcher, 2012;Lan & Fan, 2019;Noori et al, 2017). Knowing how literate teachers on LAL also indicates how high the need for teachers professional training on this topic (Anam & Putri, 2021;Latif, 2021;Ogan-Bekiroglu & Suzuk, 2014;Prasetyo, 2018;Widiastuti et al, 2020;Yan & Fan, 2021). Widiastuti et al (2020) revealed teachers with high professional development (PD) participation levels have stronger formative assessment beliefs than those with lower PD involvement.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that further explanatory study may be beneficial in gaining a deeper understanding of the different CBLAL's nature and purpose between ETs and NTs. As most of the previous studies investigated pre-service EFL teachers' LAL (Anam & Putri, 2021;Prasetyo, 2018;Viengsang, 2016), knowing the different CBLAL levels between NTs and the ETs could provide more information about the need to have professional development (PD) in this regard. To bridge that gap, we investigated the CBLAL level of two stakeholder groups; ETs and NTs, and their needs of a PD based on the level of CBLAL.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the teachers had a sound understanding of language assessments' knowledge, skills, and principles. Furthermore, Prasetyo (2018) researched a student-teacher experience of teaching practice in one of the senior high schools in Yogyakarta. It was found that the teacher got more experience in administrative tasks than guidance in teaching and assessment.…”
Section: Introductionmentioning
confidence: 99%